Fenomena Loss of Purpose pada Generasi Z dalam Perspektif Tafsir Al-Misbah Karya Quraish Shihab - Tantri Rizky Alviani; Syukri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The phenomenon of loss of purpose among Generation Z has emerged as a significant psychological issue, characterized by the absence of direction, meaning, and purpose in life as a result of various pressures associated with modern living. This study aims to analyze the concept of life's purpose in Tafsir Al-Misbah by M. Quraish Shihab and examine its relevance to the phenomenon of loss of purpose among Generation Z. This research employs a library research method using a qualitative approach and the tahlili (analytical) method of Qur'anic interpretation. The primary data source is Tafsir Al-Misbah by M. Quraish Shihab, while secondary data are drawn from books, scholarly journal articles, and other relevant literature. The findings reveal that the concept of life's purpose in Tafsir Al-Misbah encompasses five principal dimensions: human beings are created to worship Allah (QS. Adh-Dhariyat [51]: 56), humans are appointed as vicegerents (khalifah) on earth (QS. Al-Baqarah [2]: 30), life is a test to attain the best deeds (QS. Al-Mulk [67]: 2), inner peace is achieved through the remembrance of Allah (dhikr) (QS. Ar-Ra'd [13]: 28), and the ultimate orientation of life is to attain the pleasure of Allah (QS. At-Tawbah [9]: 72). These five dimensions are highly relevant to the phenomenon of loss of purpose among Generation Z, as they provide a meaningful direction in life, foster a sense of responsibility, strengthen awareness of humanity's ultimate purpose, cultivate inner tranquility, and develop a life orientation centered on seeking the pleasure of Allah. Therefore, the concept of life's purpose presented in Tafsir Al-Misbah offers a religio-spiritual foundation that can assist Generation Z in overcoming the phenomenon of loss of purpose.